A study on the factors that affecting the total compensation of land acquisition at Kelantan / Siti Nur Amirah Zuraiju - Zuraiju, Siti Nur Amirah (Bachelor of Science (Hons.) Statistics, 2015)
Jabatan Ketua Pengarah Tanah dan Galian (JKPTG) is one of the government organization to handle land cases which about Federal Land and Land Acquisition. JKPTG was about to deal with variety of people to ensure that there’s no issues existed especially when it is about payment. Every end of year, discussion will be held between firm and those related to the land acquisition or federal land cases for compensation value. This discussion will be handled by top management. However, the discussions cannot easily being agreed or deal as some of people hard to satisfy with what being decided by the firm. So, this research is about to study the factors that affecting the amount of compensation for land acquisition for federal projects. The variables involved are limited (Area, Lots Number and District). Multiple Linear Regression analysis was used to determine the factors that give influential towards the amount of compensation for land acquired. Besides that, it also about to state the best model produced from this analysis